2021
DOI: 10.7717/peerj.10932
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of AHL gene family and their expression under drought stress and ABA treatment in Populus trichocarpa

Abstract: The AT-hook motif nuclear-localized (AHL) family is a plant transcription factor family, which plays an important role in growth and development and stress responses. We identified and analyzed 37 AHL genes in poplar (Populus trichocarpa). Phylogenetic analysis classified the PtrAHL members into three subfamilies based on their conserved domain. All PtrAHL paralogous pairs evolved under purifying selection. The promoter analysis revealed the presence of stress-related and phytohormone-related cis-elements of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 50 publications
5
19
0
Order By: Relevance
“…Among them, R-G-R-P is the core sequence shared by the two motifs ( Figure 2 ). This finding is consistent with previous reports of the AHL structure ( Zhao et al, 2014 , 2020 ; Bishop et al, 2020 ; Wang et al, 2021a ).…”
Section: Resultssupporting
confidence: 94%
“…Among them, R-G-R-P is the core sequence shared by the two motifs ( Figure 2 ). This finding is consistent with previous reports of the AHL structure ( Zhao et al, 2014 , 2020 ; Bishop et al, 2020 ; Wang et al, 2021a ).…”
Section: Resultssupporting
confidence: 94%
“…The AHL is a group of transcriptional regulators with a highly conserved structure in the plant kingdom and extensive information demonstrates function in plant growth and development as well as stress responses 46 . A previous study identified 37 AHL genes in Populus trichocarpa that expression levels of these genes were induced by drought stress 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate that Lchi22185 may have lost its conserved domain during evolution. Previous studies have shown that there are 28 AHL s in Arabidopsis, 63 family members in soybean [ 5 ], 37 AHL s in popular [ 6 ], 14 in grape [ 4 ], 37 family members in maize [ 1 ] and 47 AHL genes in carrot [ 38 ]. In our study, we divided them into two clades, according to their characteristics and distribution of conserved domains.…”
Section: Discussionmentioning
confidence: 99%
“…The AHL gene family (AT-hook motif nuclear localized gene family) has been studied in a wide variety of plant species, such as Oryza sativa L., Arabidopsis thaliana , Gossypium raimondii , Zea mays , Vitis vinifera , Glycine max L. Merr, Populus trichocarpa and others [ 1 , 2 , 3 , 4 , 5 , 6 ]. For example, 29 AHL gene family members were identified in Arabidopsis , and 48, 51, and 99 AHLs were identified within the G. Raimondi , G. arboretum , and G. hirsutum genomes, respectively [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation